Translated trauma, translated lives: Hungarian women Holocaust survivors in emigration - Vasvári, Louise O. (Verbum – Analecta Neolatina, 2008)
This study is part of a larger project to integrate into Holocaust discourses the voices of women survivors, which can provide valuable insights both for Holocaust studies and gender studies. I first briefly review some of the main issues relating to the need to study female Holocaust (life) writing, in order to offer a theoretical frame for the main focus of my study: a historical introduction to "literaried" testimonies of some two dozen Hungarian emigrant women, written over a span of over half a century. I will be highlighting translation and gender issues, as well as the variety of narrative techniques the authors utilize. None of the women I study published in Hungarian, even as in some cases they had original contemporary diaries or earlier drafts in that language. Hence, the first part of my title means to focus on the additional complicating issues of self translation of traumatic events by survivors who live in emigration.